EFFECT OF EXTRACTION METHOD ON ANTIOXIDANT ACTIVITY OF PALM PALM LEAVES (Elaeis guineensis Jacq.) - Fahrauk Faramayuda; Ari Sri Windyaswari; Yeni Karlina; Muhamad Raihan Maulana; Rizka Khoirunnisa Guntina (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Oil palm (Elaeis guineensis Jacq.) is a plant that is native to Africa and South America. This plant can grow well in tropical areas, such as Indonesia. Indonesia is currently one of the largest producers of palm oil worldwide. As the area of palm oil plantations increases, the potential for waste from this plant continues to increase. The potential for palm oil leaf waste production in Indonesia is 658 kg dry matter/hectare/year. Palm oil leaf waste has been widely processed into organic fertilizers and animal feeds. This plant has the potential to be developed into a source of traditional medicinal ingredients. Based on the abundant sources of palm oil leaves and their pharmacological potential, palm oil leaves can be used as a source of raw materials for traditional medicine. This study aimed to compare the antioxidant activities of oil palm leaf extracts obtained by maceration and reflux to determine which extraction method produces the best antioxidant activity. Extraction was carried out using 70% ethanol solvent by maceration and reflux. The results of the phytochemical screening showed that oil palm leaves contain flavonoids, polyphenols, saponins, quinones, steroid-triterpenoids, and monoterpene-sesquiterpenes. Antioxidant activity using a UV-Visible spectrophotometer with DPPH free radicals showed that the extract obtained by maceration and reflux methods had IC50 values of 46.61 ± 1.76 ug/mL and 55.21 ± 2.91 ug/mL respectively. Therefore, extraction by maceration produces a better antioxidant activity. Keywords: Palm leaves; Traditional medicine; Extraction; Active compound stability; Antioxidant